2020
DOI: 10.1111/tbj.14116
|View full text |Cite
|
Sign up to set email alerts
|

Latissimus Dorsi flap enhancement by lipofilling as an immediate breast reconstruction technique for skin‐preserving mastectomy

Abstract: Aim To evaluate Latissimus Dorsi flap (LD) enhancement by lipofilling as an immediate breast reconstruction technique, for skin‐preserving mastectomy regarding oncological safety, fat graft resorption after radiotherapy, and patients' satisfaction. Patients and methods This is a prospective study that included female patients complaining of breast cancer. Patients were subjected to skin‐preserving mastectomy associated with Latissimus Dorsi flap enhancement by lipofilling using the multisite, and multilayer fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
5
2
Order By: Relevance
“…Regarding the postoperative patient satisfaction, the overall result of our patients including those who were satisfied 6 months postoperatively and those who were satisfied after they had another lipofilling session was 95.24%. These results are better than what was reported for conventional LD flap with AF enhancement or by endoscopy-assisted LD flap without AF enhancement [ 13 , 17 ]. Nevertheless, we have to stress that our results refer to small-sized breasts (cup size A-B) and not large breasts that may be suitable in other techniques.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Regarding the postoperative patient satisfaction, the overall result of our patients including those who were satisfied 6 months postoperatively and those who were satisfied after they had another lipofilling session was 95.24%. These results are better than what was reported for conventional LD flap with AF enhancement or by endoscopy-assisted LD flap without AF enhancement [ 13 , 17 ]. Nevertheless, we have to stress that our results refer to small-sized breasts (cup size A-B) and not large breasts that may be suitable in other techniques.…”
Section: Discussioncontrasting
confidence: 51%
“…In this study, after harvesting the muscle through our endoscopic-assisted technique, the main disadvantage was the small volume of the muscle compared with the conventional musculocutaneous LD flap. e mean volume of the muscle in our series was 228.76 ± 5756 ml, while Ahmed et al [13] reported that the mean volume of the LD flap was 446.40 ± 70.89 ml.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations